Relationship of advertising appeal towards purchase intention of generation Y’s on online cosmetic product. / Siti Sofea Md Sazali - Md Sazali, Siti Sofea (Faculty of Business and Management, 2017)
Marketer and advertiser concerns on how they can make their advertisement more effective and efficient through applications of appeals because it is important. Using different type of advertising appeals, are found very effective for marketing strategies especially in online marketing. People may have interest and spend time to watch such type of advertisings which give information about specifications and products features and subsequently having an intention to purchase the product. In this study, level of purchase intention is being measured, a relationship between purchase intention as a dependent variable with different types of advertising appeal in online cosmetic was investigated. Celebrity endorser, rational and emotional appeal are being selected as an independent variable and had been used in this study. Data were collected from 100 respondents of gen Y by distributed questionnaire at Aeon Mall Bandaraya Melaka and the result was analysed using SPSS. To find out the significant relationship between independent variable and dependent variable, the collected data are being analysed using Reliability Analysis, Descriptive Analysis, Correlation, Coefficient and Regressions. From the research it is found that level of purchase intention on online purchase intention of cosmetic product is high among the gen Y and it have a high and significant relationship with emotional appeal. Furthermore, emotional appeal is found to be the most influence appeals towards purchase intention of gen Y on online cosmetic product.